Hepatocellular carcinoma response to transcatheter arterial chemoembolisation using automatically generated pre-therapeutic tumour volumes by a random forest-based segmentation protocol. Issue 12 (December 2019) - Khalaf, A.M.; Fuentes, D.; Morshid, A.; Kaseb, A.O.; Hassan, M.; Hazle, J.D.; Elsayes, K.M.
Abstract : AIM: To demonstrate the feasibility of correlating pre-therapeutic volumes and residual liver volume (RLV) with clinical outcomes: time to progression (TTP) and overall survival (OS) in hepatocellular carcinoma (HCC) treated with transcatheter arterial chemoembolisation (TACE). MATERIALS AND METHODS: TTP was calculated from a database of 105 patients, receiving first-line treatment with TACE. TTP cut-off for stratifying patients into responders and non-responders was 28 weeks. Pre-treatment tumour and liver volumes were correlated with the TTP and OS following treatment. Univariate cox-regression model was used to assess whether these volumes could predict TTP and/or OS. Kaplan–Meier analysis with log-rank test was used to compare the TTP between high and low volume groups for viable, necrotic, and total tumour. Kaplan–Meier analysis was performed comparing the OS of 10 patients with the longest TTP (mea n= 122 weeks) in the responder group and 10 patients with the shortest TTP (mea n= 7 weeks) in the non-responder group. RESULTS: HCC in high tumour volume groups had a shorter TTP than lesions in low tumour volume groups ( p= 0.05, p= 0.04, p= 0.02, for enhancing, non-enhancing, total tumour groups, respectively). A negative (correlation coefficient [CC] 0.3) linear correlation between TTP and tumour volumes, and a positive linear correlation between TTP and residual liver volumes were also demonstrated (CC 0.3). Patients with the longest TTP had a higher OS than with the shortest TTP ( p= 0.03). CONCLUSION: This demonstrates the feasibility of predicting treatment response of HCC to TACE using volumetric measurements of pre-treatment lesion and the feasibility of correlating RLV with TACE outcome data in HCC patients. Highlights: More than 80% of HCC are unresectable at the time of diagnosis. TACE is offered as a locoregional therapy for unresectable HCCs. Response prediction after initial TACE is important for treatment planning. Volumetric tumor measurements are more accurate than two dimensional measurements in predicting TACE outcomes.